Web Development with Jade - Lang, Sean; Lang, Sean (Packt Publishing, 2014)
This is a step-by step, tutorial-based book which will enable web developers to explore the functionalities of Jade and learn how to use it to write certain functions and processes for web development. This book is for web developers with at least a basic understanding of HTML and JavaScript. It will enable you to write an easier form of language that then compiles into HTML.